Microglia cytoarchitecture in the brain of adenosine A2A receptor knockout mice: Brain region and sex specificities. (1st November 2019) - Simões-Henriques, Carla; Mateus‐Pinheiro, Miguel; Gaspar, Rita; Pinheiro, Helena; Mendes Duarte, Joana; Baptista, Filipa I.; Canas, Paula M.; Fontes-Ribeiro, Carlos Alberto; Cunha, Rodrigo A.; Ambrósio, António F.; Gomes, Catarina A.
Abstract: Microglia cells exert a critical role in brain development, mainly supported by their immune functions, which predicts an impact on the genesis of psychiatric disorders. In fact, microglia stress during gestation is, for instance, associated with chronic anxiety and cognitive deficits accompanied by long‐lasting, region‐ and sex‐specific changes in microglia morphology. We recently reported that the pattern of microglia morphologic plasticity, which is sex‐determined, impacts on anxious‐like behaviour and cognition. We also reported that the pharmacologic blockade of adenosine A2A receptors (A2 A R) is able to reshape microglia morphology, in a sex‐specific manner and with behavioural sequelae. In order to better understand the role of A2 A R in the sex differentiation of microglia, we now compared their morphology in wild‐type and A2 A R knockout male and female C57BL/6 mice in two cardinal brain regions implicated in anxiety‐like behaviour and cognition, the prefrontal cortex (PFC) and the dorsal hippocampus (dHIP). We report interregional differences between PFC and dHIP in a sex‐specific manner: while males presented more complex microglia in the dHIP, microglia from females had a more complex morphology in the PFC. Surprisingly, the genetic deletion of A2 A R did not alter these sex differences, but promoted the exclusive remodelling (increase in complexity) in PFC microglia from females. These findings further support the existence of a heterogeneous microglial network, distinct between sexes and brain regions, and help characterizing the role of A2 A R in the sex‐ and brain region‐specific morphologic differentiation of microglia. Abstract : Microglia present regional sex‐specific morphological subpopulations under physiological conditions. The genetic deletion of A2A R induces a regional sex‐specific structural remodelling of the morphological subpopulations of microglia in the dorsal hippocampus and in the prefrontal cortex.